+0  
 
0
49
1
avatar

Let f(x) = 4x-5 and g(x) = 3x, find (f-g)(x)

Guest Jul 22, 2017

Best Answer 

 #1
avatar+89781 
+2

Let f(x) = 4x-5 and g(x) = 3x, find (f-g)(x)

 

I think that it is just f(x)-g(x)

=4x-5-3x

=x-5

Melody  Jul 23, 2017
Sort: 

1+0 Answers

 #1
avatar+89781 
+2
Best Answer

Let f(x) = 4x-5 and g(x) = 3x, find (f-g)(x)

 

I think that it is just f(x)-g(x)

=4x-5-3x

=x-5

Melody  Jul 23, 2017

7 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details